Training workshop on communicating weather and climate information with farmers, Same, Tanzania, September 2013 - Hansen, James (2015)
This report describes a workshop that trained roughly 40 intermediaries to adapt this approach in the Kilimajaro region of northern Tanzania. The three-day intermediary training workshop (11-13 September 2015) was followed by a two-day farmer training workshop, which gave a subset of trainees hands-on experience leading the participatory process. The workshops were planned jointly by CCAFS and World Vision-Tanzania. The first three days focused on training professionals who routinely interact with smallholder farmers in the Kilimanjaro region in northern Tanzania. The 40 participants included field staff of World Vision-Tanzania (WVT), agricultural extension officers, and Tanzania Meteorological Agency (TMA) staff. It aimed to equip World Vision staff and the government agricultural extension staff that work with them to bring climate services into the ongoing livelihood and resilience-building activities of World Vision. Six participants from the training for intermediaries were selected to serve as facilitators for a two-day training and planning workshop with about twenty farmers from the surrounding district. The farmer workshop served as a practicum for the intermediary training and provided an opportunity for the participating organizations (agricultural extension, TMA, WVT) to assess the effectiveness of the approach and identify opportunities to improve the process. The report concludes with a number of suggestions for improving the intermediary training, and communication process with rural communities, with a view to upscaling climate services through WVT, TMA and agricultural extension.